Performance of electron, photon and muon triggers at the CMS High Level Trigger - Tomei, Thiago R. F. P. [UNESP] (My University, 2015)
The trigger systems of the LHC detectors play a crucial role in determining the physics capabilities of the experiments. A reduction of several orders of magnitude of the event rate is needed to reach values compatible with the detector readout, offline storage and analysis capabilities. The CMS experiment has been designed with a two-level trigger system: the Level 1 (L1) Trigger, implemented on custom-designed electronics, and the High Level Trigger (HLT), a streamlined version of the CMS reconstruction and analysis software running on a computer farm. Here we will present the design and performance of the main muon, electron and photon triggers, in view of the more challenging conditions for the LHC Run 2. For the muon case, we discuss the improvements in the isolation algorithm with the usage of Particle Flow techniques, which allow for better discrimination power between processes with prompt muons and the the effect of jets penetrating through the hadronic calorimeter into the muon chambers. For the electron and photon cases, we discuss the identification variables used to distinguish between prompt electrons/photons and hadronic jets enriched in electromagnetic component.